Predicting Obstructive Sleep Apnea Status With the Reflux Symptom Index in a Sleep Study Population. (2nd March 2020) - Teklu, Meron; Gouveia, Christopher J.; Yalamanchili, Amulya; Ghadersohi, Saied; Price, Caroline P. E.; Bove, Michiel; Attarian, Hrayr P; Tan, Bruce K.
Abstract : Objectives/Hypothesis: Otolaryngologic symptoms of obstructive sleep apnea (OSA) and their diagnostic utility are not well studied. We aimed to elucidate the prevalence of otolaryngologic symptoms among patients being evaluated for OSA. Given findings that the Reflux Symptom Index (RSI) was strongly associated with OSA status, we evaluated the diagnostic utility of the RSI for predicting OSA status. Study Design: Cross‐sectional. Methods: We recruited 101 adults presenting for ambulatory polysomnograms to the Northwestern Sleep Disorders Center from July 2017 to July 2018. The Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Leicester Cough Questionnaire (LCQ), RSI, Gastroesophageal Reflux Disease Questionnaire, Sino‐Nasal Outcome Test‐22, Nasal Obstruction Symptom Evaluation, Eustachian Tube Dysfunction Questionnaire 7, and Headache Impact Test were administered. Polysomnogram results were subsequently obtained. Patients with OSA (apnea‐hypopnea index ≥ 5) and without OSA were compared. Results: Of the 101 participants, 98 had valid sleep study results. Of those, 72 were diagnosed with OSA and 26 were not. The two groups differed significantly in age and body mass index (BMI). Of the questionnaires, only the RSI and LCQ means differed significantly, with worse symptoms in the OSA group ( P = .003 and .014, respectively). Upon univariate regression, age, BMI, and RSI were associated with OSA status. Using regression coefficients, a clinical score of 2 (RSI) + 1.5 (BMI) + age yielded a diagnostic model (C‐statistic = 0.807, P  < .001). A threshold score of 104.21 was 76.4% sensitive and 73.1% specific. Conclusions: Patients with OSA have worse symptoms of laryngopharyngeal reflux as measured by the RSI. The addition of the RSI to the recognized factors of age and BMI improves diagnostic utility for OSA. Level of Evidence: 2 Laryngoscope, 2020